The Adenosine Analogue NITD008 has Potent Antiviral Activity against Human and Animal Caliciviruses - Daniel Enosi Tuipulotu; Tulio M. Fumian; Natalie E. Netzler; Jason M. Mackenzie; Peter A. White (Viruses, 2019)
The widespread nature of calicivirus infections globally has a substantial impact on the health and well-being of humans and animals alike. Currently, the only vaccines approved against caliciviruses are for feline and rabbit-specific members of this group, and thus there is a growing effort towards the development of broad-spectrum antivirals for calicivirus infections. In this study, we evaluated the antiviral activity of the adenosine analogue NITD008 in vitro using three calicivirus model systems namely; feline calicivirus (FCV), murine norovirus (MNV), and the human norovirus replicon. We show that the nucleoside analogue (NA), NITD008, has limited toxicity and inhibits calicivirus replication in all three model systems with EC50 values of 0.94 μM, 0.91 µM, and 0.21 µM for MNV, FCV, and the Norwalk replicon, respectively. NITD008 has a similar level of potency to the most well-studied NA 2′-C-methylcytidine in vitro. Significantly, we also show that continual NITD008 treatment effectively cleared the Norwalk replicon from cells and treatment with 5 µM NITD008 was sufficient to completely prevent rebound. Given the potency displayed by NITD008 against several caliciviruses, we propose that this compound should be interrogated further to assess its effectiveness in vivo. In summary, we have added a potent NA to the current suite of antiviral compounds and provide a NA scaffold that could be further modified for therapeutic use against calicivirus infections.